Familiar perception about critical cardiovascular patient - Uribe Escalante, María Teresa; Muñoz Torres, Carolina; Restrepo Ruiz, Juliana (Investigación y Educación en Enfermería, 2008)
The study was conducted in february 2003 within 15 close relatives to critical cardiovascular patients in intensive therapy at Bolivariana Hospital. It was a retrospective, interpretative and phenomenological research. We considered the feelings of the relatives aroused by manifest responses. We found that almost all were women, married and housewifes, between 31 and 50 years old, of the so called ";estrato 2"; in the socioeconomic classification of the population and Catholics. Their children were pre-schooling and teenagers, their aim was to maintain rationalization, moral, physical fitness and order. It allows to understand the great esteem held for the sick familiars; but they felt insufficiently cared for and they spontaneously expressed fear and sadness. Their feelings were revived no matter the time. Expectations were hope and death’s perception. There was affliction, anguish, faith or God’s hope. Fortitude or disregard about the relative´s illness was explained properly by some, meanwhile others repeated what they just heard; and many expressed preoccupation, anxiety and specially a great responsibility about taking decisions. Most relatives felt satisfied about the way their parents were handled, and also felt satisfaction with the space given to talk about their experiences. Finnaly it deals with a proposal about emotional alphabetization to the personnel which participate in the process and interact with relatives. Key words: phenomenology, sentiments, intensive care, critically ill patients, care given